Genetic and biotechnological characterization of folate-producing probiotics isolated from local dairy products - Rahma Ali Hassan Abubakr; Mohammed Hassan Abdel A’al; Gihan Mohamed El Moghazy; Ashraf Bakry Abd Elrazik; Samir Abdel Aziz Ibrahim (Beni-Suef University Journal of Basic and Applied Sciences)
Abstract Background Folate is essential for Deoxyribonucleic acid (DNA) synthesis, methylation and repair, with deficiencies linked to neural tube defects, Alzheimer’s, and cancer. Certain lactic acid bacteria (LAB), particularly in fermented dairy products, are natural folate producers. However, genetic insights into high-yielding strains remain limited. This study isolates indigenous lactic acid bacteria (LAB) and provides the first genetic mapping of folate biosynthesis in Streptococcus thermophilus (S. thermophilus). Methods Probiotic bacteria were isolated from locally sourced milk and yogurt samples and were subjected to morphological, biochemical, and molecular identification. The isolates were screened for folate production levels. Molecular studies and “in-silico” analysis were carried out to investigate the genetic basis of folate biosynthesis, particularly in S. thermophilus. Results Two folate-producing probiotic strains, Enterococcus faecium (E. faecium) and S. thermophilus, were isolated and characterized. Quantitative analysis revealed folate production levels of 2.2–8.3 µg/L and 156–162 µg/L, respectively, demonstrating significantly higher synthesis by S. thermophilus. In this strain, seven folate biosynthesis genes and one metabolism gene were identified and mapped. Five of the biosynthetic genes were found to be clustered: folC2 (encoding dihydrofolate synthase), folE (encoding GTP cyclohydrolase I), folP (encoding dihydropteroate synthase), folB (encoding dihydroneopterin aldolase, and folK (encoding 6-hydroxymethyl-7,8-dihydropterin pyrophosphokinase). The remaining genes were dispersed throughout the genome. A conserved Shine-Dalgarno sequence (AGGAG) was found 5 base-pair (bp) upstream of five genes. Conclusion This study elucidates the genetic basis of folate production in S. thermophilus, enabling future metabolic engineering for enhanced folate yields. The findings support strain selection for folate-enriched functional foods.